2001
DOI: 10.1002/1098-2736(200101)38:1<3::aid-tea2>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The ideal of standards and the reality of schools: Needed research

Abstract: Research potentially can assist in the process of implementing the National Science Education Standards. Existing research shows that changes called for in the Standards are difficult to put into practice, create dilemmas for teachers, require significant changes in teachers' values and beliefs, are fostered when change is pursued within departments within schools, are influenced powerfully by teacher collaboration in the work context, are often resisted strongly by parents, and often demand new student roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
12

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 16 publications
1
98
0
12
Order By: Relevance
“…(see Barton & Osborne, 1998). In studying girls' participation in a reform-based setting, this study follows recommendations made by Anderson & Helms (2001), who called for more nuanced understandings of the complexities of reform in science education and students' roles within reform-based classrooms in ordinary school contexts. However, the study raises additional questions and prompts further research.…”
Section: Resultsmentioning
confidence: 99%
“…(see Barton & Osborne, 1998). In studying girls' participation in a reform-based setting, this study follows recommendations made by Anderson & Helms (2001), who called for more nuanced understandings of the complexities of reform in science education and students' roles within reform-based classrooms in ordinary school contexts. However, the study raises additional questions and prompts further research.…”
Section: Resultsmentioning
confidence: 99%
“…Anderson and Helms (2001) point to the crucial issue of changing teachers' views of teaching and learning from transmissive towards constructivist orientation. However, research has also shown that a constructivist view, for example, as revealed in interviews, does not necessarily guarantee teaching behaviour that is constructivist oriented (Fischler, 1994).…”
Section: Research On Teachers' Views Of Teaching and Learning And Thementioning
confidence: 99%
“…Finally, the educational administration and the parents themselves can also stimulate change in the teacher, or indeed hinder it if those changes do not respond to their conception of what is good teaching or if the initial rates of learning do not come up to their expectations (Bencze and Hodson 1999;Anderson and Helms 2001).…”
Section: Models Of Conceptual Changementioning
confidence: 99%
“…Teacher education programs have to treat the teacher as an integral member of a group, providing collective development experiences and encouraging collaboration. In sum, they must consider the school as being the most suitable place for professional development and as the unit for change Anderson and Helms 2001;Reyes et al 2001;Marcelo 2002;Ritchie and Rigano 2002;Davis 2003;Sassi et al 2005). This requires time and much sustained support before the teacher can see the improvement in the pupils' learning and perceive ongoing education as a meaningful experience personally, for his or her classes, and for the school Tal et al 2001;Peers et al 2003).…”
Section: Teachers' Personal and Social Development Together With Theimentioning
confidence: 99%